When the world collapses: changed worldview and social reconstruction in a traumatized community - Čorkalo Biruški, Dinka (Array, 2011)
Traumatic experience can affect the individual's basic beliefs about the world as a predictable, safe and coherent place in which the value of an individual is granted. One of the cornerstones in recovery from trauma is the reestablishment of the shattered worldview. This study looked at the role of the changed worldview in the relationship between war-related traumatic experiences and readiness for social reconstruction as defined by three processes: inter-group rapprochement, rebuilding of trust and need for apology. The study included a community sample of 333 adults (18-65), Croats and Serbs living in the city of Vukovar, the community in Croatia that was most devastated during the war (1991-1995). The hypothesis was that the people more affected by traumatization are less ready for social reconstruction, but that this relationship is mediated by the changed worldview. Mediation analyses showed that in both ethnic groups the worldview fully mediated between traumatic experiences (measured by IES-R) and the overall score for readiness for social reconstruction and the inter-group trust. However, the changed worldview was not a decisive mediator between symptoms of traumatization and inter-group rapprochement and need for apology from the other group. The implications of these findings for rebuilding inter-ethnic relations in communities affected by war will be discussed.